Cell membrane coated nanoparticles: next-generation therapeutics. (November 2017) - Narain, Ashwin; Asawa, Simran; Chhabria, Vikesh; Patil-Sen, Yogita
Cell membrane coated nanoparticles (NPs) is a biomimetic strategy developed to engineer therapeutic devices consisting of a NP core coated with membrane derived from natural cells such as erythrocytes, white blood cells, cancer cells, stem cells, platelets or bacterial cells. These biomimetic NPs have gained a lot of attention recently owing to their cell surface mimetic features and tailored nanomaterial characteristics. They have shown strong potential in diagnostic and therapeutic applications including those in drug delivery, immune modulation, vaccination and detoxification. Herein we review the various types of cell membrane coated NPs reported in the literature and the unique strengths of these biomimetic NPs with an emphasis on how these bioinspired camouflage strategies have led to improved therapeutic efficacy. We also highlight the recent progress made by each platform in advancing healthcare and precis the major challenges associated with these NPs.